Praktik Julo-Julo Nomor Nol dalam Tinjauan Fiqih Muamalah di Jorong Kapeh Panji Kecamatan Banuhampu - Rizka Nurmala Cahyani; Sofia Ridha (Lembaga Yasin AlSys, 2026)
The practice of julo-julo nomor nol in Jorong Kapeh Panji, Banuhampu Subdistrict, reflects the dynamics of community-based financial transactions that use money as the main object. The uniqueness of this practice lies in the assignment of number zero to the administrator as compensation for management and as a reserve fund in the event of delayed payments by members. This study aims to determine the mechanism of the julo-julo nomor nol practice and to review its conformity with fiqh muamalah. This study used field research with a qualitative approach. Data were obtained through interviews, observation, and documentation involving the administrator and members of julo-julo in Jorong Kapeh Panji, Banuhampu Subdistrict, and were then analyzed descriptively to understand the implementation of this practice from the perspective of Islamic law. The results showed that julo-julo was implemented through a lottery system to determine the order of fund recipients, except for number zero, which was directly given to the administrator. In principle, this practice can be justified in fiqh muamalah because it uses an ujrah contract that fulfills the valid requirements, such as willingness, agreement, and clarity of the contract object. In addition, julo-julo provides social and economic benefits for the community, particularly as a means of saving and strengthening social relations among members. However, its implementation still contains an element of injustice because the amount of additional contributions differs according to the number of entries followed by each member. The conclusion of this study emphasizes that the practice of julo-julo nomor nol needs to be improved because, in its implementation, it is categorized as a fasid contract due to its contradiction with the principle of justice in Islam and its potential to cause harm. The implications of this study indicate the importance of managing community financial practices transparently, fairly, and in accordance with sharia provisions.